Dentro e fora da ordem : diretrizes curriculares para o ensino de História em tempos autoritários (1964-1985) - Luiz, Miriã Lúcia (2015)
This study investigates the outline of history as a teaching and learning subject in the State of Espírito Santo, Brazil during the military dictatorship (1964-1985). For this purpose, it analyzes curricular propositions, pedagogical material, attendance lists, class activities, evaluation instruments, photographs, reports, coursebooks, student-teacher programs, minutes of meetings, laws, legal opinions, decrees, local news articles and teachers oral reports. This study is mainly based on Marc Bloch (2001) and Carlo Ginzburg (2002, 2004, 2007) to obtain data according to the following question: How did curricular guidelines for History teaching unfold in schools during the Military Dictatorship in Brazil (1964-1985)? The study analyzes the sources according to these axes: a) the concepts of history, its teaching and learning as per curricular guidelines proposed during the dictatorial regime (1964-1985); b) the perspective of teaching by teachers who worked in Espirito Santo schools during the military regime; c) teachers’ perception about curricular prescriptions and its uses in history teaching in public Espirito Santo schools during the dictatorial period. The state documents and records found show the concept of history related to social studies; and the essentially political and Eurocentric features of history teaching. They are close to the MEC (Ministry of Education and Culture) Book: History of Brazil and General History because of the traditional characteristics they present. However, they differ from the second document, which is linked to New History. As far as teaching is concerned, the proposals, records, and teachers’ narratives, the methods gained fundamental importance. They were connected to the New School and Technicist matrix, and to the Jean Piaget’s principles of Genetic Epistemology. The citizenship and patriotism identified in the study are stressed by subjects Moral and Civic Education, Brazilian Social and Political Organization, and Studies on Brazilian Problems, which were included in the school curriculum as per Law no. 5.692/71. On the other hand, there are narratives and activities that differ from the prescriptions and from what historiography shows about history teaching during the military dictatorship. Therefore, by crossing the sources analyzed — documents and narratives of subjects who worked during the military regime — we can now light up the memories and history of Espirito Santo teachers and their practice